Living well with a serious illness a guide to palliative care for mind, body, and spirit - Kanarek, Robin B. (Baltimore Johns Hopkins University Press, 2023)
A practical guide for understanding how palliative care can improve quality of life for patients and their caregivers.Robin Bennett Kanarek was a registered nurse working with patients suffering from chronic medical conditions when her ten-year-old son was diagnosed with leukemia. As her son endured grueling treatments, Robin realized how often medical professionals overlook critical psychological, emotional, and spiritual support for people with life-threatening illnesses. Living Well with a Serious Illness is the culmination of decades of Robin's work to advance the field of palliative care.Although palliative care is often associated with hospice and end-of-life planning, Kanarek argues for a more expanded definition that incorporates palliative care earlier in patients' journeys. Living Well with a Serious Illness helps patients and their caregivers understand what palliative care entails how to access the support they need when going through a serious illness what questions to ask medical professionals how to navigate advanced care planning definitions of common terminology used with end-of-life planning the importance of spiritual care, coping strategies, and emotional support how to become an advocate for palliative careThis book illuminates the importance of seeing patients as individuals who can benefit from care for their body, mind, and spirit-the core tenet of palliative care
Introduction: David's Story-- What is palliative care?-- Barriers to palliative care: taking care of the person versus fighting the disease-- How we want to die: palliative care's benefits for patients and their loved ones-- How to get the care you want: knowing what to ask for, what to expect, and what to demand-- How to cope when illness changes everything: quality-of-life care includes the family-- Putting it all together: creating an action plan for when the end is near-- Spirituality and well-being: care of the spirit matters too-- Grief: tapping into restorative sources after goodbye-- Making palliative care mainstream: what legislators, philanthropists, educators, and you can do-- Epilogue: David's legacy-the kanarek family foundation-- Resources.
Includes bibliographical references (pages 189-199) and index.
Keywords: Terminal care .; Palliative treatment; Families of the terminally ill -- Psychology